The Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd004899
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type A therapy for hemifacial spasm

Abstract: BackgroundThis is an update of a Cochrane Review, first published in 2005.Hemifacial spasm (HFS) is characterised by unilateral, involuntary contractions of the muscles innervated by the facial nerve. It is a chronic disorder, and spontaneous recovery is very rare. The two treatments routinely available are microvascular decompression and intramuscular injections with botulinum toxin type A (BtA). ObjectivesTo compare the e icacy, safety, and tolerability of BtA versus placebo in people with HFS. Search method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
0
25
0
2
Order By: Relevance
“…Although botulinum neurotoxin injections are currently the mainstay of therapy, other therapies are on the horizon. 17,38,46,63,64 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although botulinum neurotoxin injections are currently the mainstay of therapy, other therapies are on the horizon. 17,38,46,63,64 …”
Section: Discussionmentioning
confidence: 99%
“…Although neurosurgical treatment is available, the potential complications and relatively high recurrence rate have made botulinum toxin A the preferred symptomatic treatment for HFS. [34][35][36][37][38][39] As HFS rarely remits spontaneously, 40 most patients need to continue BoNT-A treatment for many years, if not for the rest of their lives. The long-term efficacy and safety of BoNT-A are, therefore, increasingly important questions.…”
Section: Introductionmentioning
confidence: 99%
“…Our data clearly indicate that BTA treatment is a relatively lowcost treatment when injections are performed in the small muscles (face, upper limb). Several metaanalyses have shown that BTA treatment is effective in facial dystonia, facial hemispasm [5][6][7]13], and cervical dystonia [6,19]. In the latter, treatment cost is higher but BTA offers a real functional gain in these severely distressed patients, with significant improvement in clinical symptoms, associated pain, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Spasmus hemifacialis werden mit Botulinumtoxin A Responderraten zwischen 76-100% erreicht (19). Praktisch alle der zahlreichen Studien wurden ohne EMG-Kontrolle durchgeführt.…”
Section: Blepharospasmus Und Spasmus Hemifacialisunclassified